Pengembangan Sistem Simulasi Ujian Nasional Sekolah Menengah Atas (SMA) Online Berbasis Web - Sakethi, Dwi; Pribadi, Irwan Adi; Destiana, Ririn (Universitas Lampung, 2014)
The national exam is a method of testing to education in Indonesia for determining students graduation in senior high school. The determine graduate base on the minimum value that must be obtained by students and established by the government. Students follow the simulated exam before faced the national exam for value of the capability test.Â The purpose in this research is develop a simulation system the national exam for senior high school students with a web-based, so it can be accessed online. In addition, the purpose in this research to build the another alternative in simulation exams except in the school. Development systems using the programming languagePHP and the MySQL database.Â The testing system indicates that the system can function properly when doing the process simulation test and get the results right after finish working on problems such as the simulation test.Â Keywords: National Exam, Simulation System, Web.